2022
DOI: 10.3389/fneur.2022.976089
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic system dysfunction in patients with early chronic kidney disease

Abstract: IntroductionIt is a recent finding that glymphatic system dysfunction contributes to various neurological problems. The purpose of this research was to assess the function of the glymphatic system in neurologically asymptomatic early chronic kidney disease (CKD) patients and healthy controls, using diffusion tensor image analysis along perivascular space (DTI-ALPS) index.MethodsIn a prospective study, we included patients with early CKD who were asymptomatic for neurological issues and obtained clinical and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…With evidence from bench to clinical, impairment of aquaporin function leads to kidney diseases [ 40 ]. Impaired glymphatic activity was observed in chronic kidney disease, from mild to advanced stages [ 41 , 42 ]. Besides, our results also support this renal-brain association in water metabolism that blood Cr and BUN correlated with the DTI-ALPS index.…”
Section: Discussionmentioning
confidence: 99%
“…With evidence from bench to clinical, impairment of aquaporin function leads to kidney diseases [ 40 ]. Impaired glymphatic activity was observed in chronic kidney disease, from mild to advanced stages [ 41 , 42 ]. Besides, our results also support this renal-brain association in water metabolism that blood Cr and BUN correlated with the DTI-ALPS index.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a recent study suggests that the glymphatic system may be suppressed in early CKD [43] . In addition, cerebral blood flow has been identified increased in CKD [44] , possibly through endothelial or glial cells, which may change the way substances exchanged between blood and neurons, causing the impairment of the blood-brain barrier and glymphatic system.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause cerebral hypoxia, which may likewise induce cognitive dysfunction [ 223 ]. A study by Chang Min Heo and his team showed that patients with chronic kidney disease already have dysfunction of the glymphatic system in the early stages of the disease [ 222 , 224 ]. This is mainly due to two factors.…”
Section: The Critical Role Of the Cerebral Lymphatic System As A Brid...mentioning
confidence: 99%